Fact-Checking Practice Regarding Information of Covid-19 Pandemic on Tempo.co, Tirto.id, and Kompas.com - YA Nunung Prajarto (BPSDMP Kominfo Manado, 2021)
Infodemics and Coronavirus hoaxes during the period of Covid-19 pandemic are circulating freely and massively in Indonesia. Although information widens opportunities for public to understand the dangers of Coronavirus, this raises concerns about the accuracy and clarity of existing information and pushes verified media to operate fact-checking. This content analysis reseach was conducted towards factchecking practices of 174 pandemic information published by Tempo.co, Tirto.id, and Kompas.com in March-May 2020 by elaborating fact-claims, fact-checking process, and forms of missinfodemics which leads to unnderstand that fact-checking is a complex process. First, the domination of contect fabrication and manipulation on fact-checking shows innacurate narratives on infodemics. Second, practice of fact-checking journalism is clearly addressed to verify information. Third, media have become attractive and collaborative storytellers in verifying information.